FAMILY COMMUNICATION AND SELF-INJURIOUS BEHAVIOUR IN COLLEGE STUDENTS: THE MEDIATING ROLE OF EMOTIONAL NEGLECT - Saleem, Sadia; Zahra, Sayyeda Taskeen; Karamat, Anum; Mahmood, Zahid (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the mediating role of emotional neglect between family communication and self-injurious behaviour. Methods: in this cross sectional study, total 312 college students from an urbanized city of Lahore were surveyed using the Family Communication Scale, the Emotional Neglect Scale, and the Self-injurious Behaviour Scale. Data were entered and analysed with the help of SPSS version 19. The relationships among family communication, emotional neglect, and self-injurious behaviour were explored through the Pearson Product-Moment Correlation. Mediation Analysis was carried out on PROCESS using Hayes Model. Results: The correlation analysis showed a significant negative relationship among family communication, emotional neglect, and self-injurious behaviour and a significant positive relationship between emotional neglect and self-injurious behaviour. Mediation analysis revealed that emotional neglect fully mediated the relationship between family communication and self-injurious behaviour Conclusion: Emotional neglect is a significant risk factor for the mental health of an individual, especially if it occurs in a family set up.